Combination of ketamine and fentanyl (KetaFent) for safe insertion of ultrasound-guided central venous catheters in infants - D’Andrea, Vito; Prontera, Giorgia; Barone, Giovanni; Vento, Giovanni (Frontiers in Pediatrics, 2023)
Centrally inserted central catheters (CICCs) are placed by ultrasound guided puncture of the internal jugular or brachio-cephalic vein. It is crucial to achieve a good level of sedation and analgesia in order to keep the babies still thus reducing the risk of procedural failure. The aim of this study is to evaluate the efficacy of the combination of ketamine and fentanyl during the CICC placement procedure. We retrospectively collected data from 72 infants who underwent CICC insertion after sedation with KetaFent protocol. The primary outcome was to assess the success of the procedure defined as CICC placement. Secondary outcome was intubation during the procedure in non-ventilated infants (noninvasive ventilation or spontaneous respiration), need for repeat doses of study medications to complete the procedure, time to complete the procedure, the level of analgesia assessed using vital parameters. The procedure was completed in 100% of cases. There were no cases of hypotension during and at the end of the procedure. No intubation was performed on non-ventilated infants. The combination of ketamine and fentanyl for sedation and analgesia in infants requiring insertion of a CICC is 100% successful. It is associated with a low risk of side effect like apnea and intubation. Insertion of a central venous catheter is a painful procedure for infants. Adequate sedation is mandatory to keep the baby still thus reducing the risk of procedural failure.